ANALISIS STRATEGII PEMASARANI DI PT. ACEI HARDWAREI CABANGI DEPOK - Nur El Ikhsan; Mercy S Devina dei Fretes; Rizky Pandiansyah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims at determining the role of SWOT analysis in facing market competition during the Covid-19 Pandemic. The problem in this research is “How does SWOT analysis play a role in facing market competition during the Covid-19 Pandemic at PT. ACE Hardware Depok Branch.” The research methods used are descriptive analysis research method, SWOT Matrix, External Factor Evaluation-EFE Matrix, and Internal Factor Evaluation-IFE Matrix. The results of the research show that the competitive strategy currently implemented by PT. ACE Hardware Depok Branch does not only provide quality products at affordable prices but also considers maximum delivery services, makes maximum use of product sales through social media, and maintains the company's image in public so as to increase customer loyalty. The weighted value of Internal Factor Evaluation Matrix (IFE Matrix) is 2.85 which indicates that the position of PT. ACE Hardware Depok Branch has a very strong internal position. Meanwhile, the weighted value of the External Factor Evaluation Matrix (EFE Matrix) is 3.02 which indicates that PT. ACE Hardware Depok Branch, in facing the dynamics of the external environment the company's position, is relatively strong.